2013
DOI: 10.1016/s2221-1691(13)60147-1
|View full text |Cite
|
Sign up to set email alerts
|

The aflatoxin B1 isolating potential of two lactic acid bacteria

Abstract: Strains of Lactobacillus pentosus and Lactobacillus beveris were isolated from human feces and local milk samples, respectively. And both strains has the ability to isolate or bind with aflatoxin B1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 20 publications
(22 reference statements)
0
18
0
1
Order By: Relevance
“…Elsanhoty et al () used the probiotics for detoxification of aflatoxin B2. Other studies used two lactic acid bacteria: L. pentosus and L. beveris in detoxification of B1 afalatoxin (Hamidi et al, ; Oluwafemi et al, ; Saladino, Luz, & Manyes, ). Moreover, Soccol et al () used both of lactobacillus and yeasts in aflatoxin remediation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elsanhoty et al () used the probiotics for detoxification of aflatoxin B2. Other studies used two lactic acid bacteria: L. pentosus and L. beveris in detoxification of B1 afalatoxin (Hamidi et al, ; Oluwafemi et al, ; Saladino, Luz, & Manyes, ). Moreover, Soccol et al () used both of lactobacillus and yeasts in aflatoxin remediation.…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxins are secondary metabolites of fungi and presence of mycotoxins in food can cause many of nutritional hazards. It was reported that more than 10% of the populations in industrial nations annually suffer from food source-related sicknesses (Elsanhoty, Ramadan, El-Gohery, Abol-Ela, & Azeke, 2013;Hamidi et al, 2013;Reddy et al, 2010;Yabe & Nakajima, 2004). It well known that aflatoxins can cause chronic effects for the human especially infants such as hepatitis, liver cancer, hepatomegaly, and cirrhosis (Azizollahi Aliabadi et al, 2013;Celikt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a great chance for reducing the presence of AFs in food products through the utilization of certain types of nonpathogenic bacteria such as the group of LAB. Also, utilization of LAB as a food supplement or probiotic products preventing the absorption of AFB1 in human and animal bodies as they have the ability for binding and isolating AFB1 (Farber et al, 2000 andHamidi et al,2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dentre as aflatoxinas, a aflatoxina B 1 (AFB 1 ) é considerada potencialmente mais tóxica, sendo classificada como um composto altamente carcinogênico, teratogênico e mutagênico (Shim et al, 2014). Além disso, AFB 1 é capaz de suprimir o sistema imunológico e induzir citotoxicidade (Hamidi et al, 2013;Nones et al, 2013). Quando presente nos alimentos e consumida em doses elevadas, as aflatoxinas são capazes de ocasionar severas intoxicações, podendo levar os pacientes ao óbito (Mallmann et al, 2011).…”
Section: Introductionunclassified